Pengaruh Motivasi, Engagement Dan Lingkungan Kerja Terhadap Kinerja Karyawan - Darda, Ahmad; Rojikun, Ahmad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The purpose of this study was to determine the effect of motivation, employee engagement and work environment on employee performance. This study uses primary data obtained from the results of distributing questionnaires to respondents, namely employees of PT. Unggul Indah Perkasa, the questionnaire was compiled based on a Likert scale. The research data is processed by statistical analysis with classical assumption test, multiple linear regression test, hypothesis test and determinant coefficient. The population in this study were employees of PT Unggul Indah Perkasa, amounting to 200 people. Sampling using simple random sampling method, while the determination of the sample using the Slovin formula, in order to obtain 133 employees as research samples. The results showed that motivation had a significant effect on employee performance. Employee engagement has a significant effect on employee performance. The work environment has a significant effect on employee performance, and motivation, employee engagement and the work environment together have a significant effect on employee performance.